PENGARUH BIAYA PROMOSI TERHADAP PENINGKATAN PENJUALAN BUDI DAYA IKAN DI KELURAHAN PURUK CAHU KABUPATEN MURUNG RAYA PROVINSI KALIMANTAN TENGAH - periyadi Periyadi; Muhammad Haris Syafitri; Junaidi Junaidi (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
The main objective of this research is to study and analyze (1) The influence of promotion cost which consist of advertising cost, promotion cost of sale and cost of public relation and reporting, have significant influence either partially or simultaneously. (2) The dimension of promotional cost which is greater the effect on the increase of the sale of fish cultivation by farmer group of cooperation. This research is done by quantitative method and also use analysis method with SPSS Windows For Data as a data analysis tool. Based on the result of the research, it is found that in the multiple linear regression analysis it is found that promotion cost consisting of advertising cost, sales promotion cost and public relation cost and reporting, have significant influence either partially or simultaneously to the increase of fish farming sale by farmer group of pakat sasama.